2012
DOI: 10.1242/jcs.090464
|View full text |Cite
|
Sign up to set email alerts
|

Orai1 deficiency leads to heart failure and skeletal myopathy in zebrafish

Abstract: SummaryMutations in the store-operated Ca 2+ entry pore protein ORAI1 have been reported to cause myopathies in human patients but the mechanism involved is not known. Cardiomyocytes express ORAI1 but its role in heart function is also unknown. Using reverse genetics in zebrafish, we demonstrated that inactivation of the highly conserved zebrafish orthologue of ORAI1 resulted in severe heart failure, reduced ventricular systolic function, bradycardia and skeletal muscle weakness. Electron microscopy of Orai1-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 39 publications
9
44
0
Order By: Relevance
“…Our observation that STIM1 deficiency leads to dilated cardiomyopathy is supported by reports in the zebrafish, where inactivation of the Orai1 ortholog leads to heart failure and impaired mechanosignal transduction (39). In addition, Horton et al (15) have shown that mice deficient in Orai1 develop a dilated cardiomyopathy that was associated with reduced survival without any evidence of cardiac hypertrophy.…”
Section: Discussionsupporting
confidence: 84%
“…Our observation that STIM1 deficiency leads to dilated cardiomyopathy is supported by reports in the zebrafish, where inactivation of the Orai1 ortholog leads to heart failure and impaired mechanosignal transduction (39). In addition, Horton et al (15) have shown that mice deficient in Orai1 develop a dilated cardiomyopathy that was associated with reduced survival without any evidence of cardiac hypertrophy.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, a similar combination of symptoms was observed in a genetically unresolved patient with a histopathological diagnosis of MmD, reported before the identification of the Orai1 gene [91]. Cells isolated from patients carrying mutations causing reduced Orai1expression display impaired Ca 2+ influx while in zebrafish lack of Orai1 leads to loss of skeletal (and cardiac) muscle integrity and myofibrillar disruption [92].…”
Section: Disorders Of Soce: Tubular Aggregate Myopathysupporting
confidence: 59%
“…Furthermore, in Orai1-deficient cardiomyocytes, the calcineurin-associated protein calsarcin was lost from the z-discs and mechanosignal transduction was impaired (131). Although these data support the notion that defects in SOCE are associated with significant cardiovascular complications, it should be noted that humans and mice with reduced STIM1 expression primarily exhibit extensive immunodeficiency and skeletal muscle pathology, with no signs of overt cardiovascular pathology (21).…”
Section: Orai1/trpcmentioning
confidence: 86%
“…Of note, inactivation of the Orai1 ortholog in zebrafish resulted in the development of heart failure and progressive loss of skeletal muscle myofiber integrity (131). Furthermore, in Orai1-deficient cardiomyocytes, the calcineurin-associated protein calsarcin was lost from the z-discs and mechanosignal transduction was impaired (131).…”
Section: Orai1/trpcmentioning
confidence: 99%